STREET SKATERS: FACING UNCERTAINTY AND BUILDING KNOWLEDGE (Fiep Bulletin - online, 2011)
Street skaters practitioners, shifting by the spaces of the city stimulate creativity and extemporaneous remark. The practice of self-learning when performed with its own method may inspire a planetary education. Reading and creating its own obstacles, taking fast decisions in action, taking the risk of maneuvers full of uncertainty in order to overcome them; this customer uses the method as an expanding aleatory strategies of learning and of body domain on a object that glides along the streets causing giddy pleasures. The practitioner takes advantages of his mistakes during the body maneuvers and, with the skate, makes strategy, initiative, invention and art to extend the pleasure of challenges. Enthusiasm, transgressions lived by these people indicate the presence of the Myth of Dionysius manifested as a life style. Roaming on earth, but linked to the sky, to liberty. These people reinvent and renew at each moment the complexity of their actions, in which we find constructive elements of mistakes, uncertainty and the hope to a planetary education organization by the means of daily life.
Keywords: uncertainty; construction of knowledge; method